Assesment for Learning dalam Pembelajaran Bahasa di Sekolah - Joko Nurkamto; Teguh Sarosa (Universitas Sebelas Maret, 2020)
Previous studies show that assessment for learning (AfL) is reported to give a significant impact on student academic and language skills-related performance, especially when meaningful feedback strategies are adopted. Despite this empirical evidence, in most Asian countries, AfL remains under-practiced particularly in prescribed-mandated curriculum practices where teachers are considered as curriculum transmitters, and exercise-and-test based instruction are still pedagogical rituals in the classrooms. To respond to this critical issue, in this article, we would like to explore assessment for learning (AfL) in English language teaching. It focuses primarily upon the concept of AfL, the aim of Afl, prerequisite for implementing AfL, and the enactment of AfL for classroom practice. Since AfL practices are of great concern to curriculum policy makers, school leaders, and teacher educators, we conclude our article by offering some practical recommendations.